Strategic Management Of Population Governance In Surabaya - Simanjuntak, Maria Equina Rotua; Wibawani, Sri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Population growth is the increase in the number of people in an area. Surabaya is currently ranked as the city with the highest population in East Java. The purpose of this research is that the government wants to realize harmony, harmony and balance of population by controlling population quantity in accordance with Law No. 52 of 2009. This research method is descriptive qualitative with the object of research on Population Management Strategy in Surabaya City. The focus of this research uses the theory of Strategic Management by Fred R. David with 3 variables, namely; Strategy Formulation, Strategy Implementation and Strategy Evaluation. Data collection techniques with observation, interviews and documentation. Determination of informants in this study with Purposive Sampling and Snowball Sampling. The results of this study are 1) Strategy Formulation, the existing vision and mission are considered good by utilizing the strength of the human resources in it and the opportunities provided by the central government in carrying out the strategy so that later the lack of public awareness will be handled. 2) Strategy Implementation, with annual goals helping DP3APPKB and Dispendukcapil Surabaya in the effectiveness of resource allocation and there is good work motivation in it. 3) Strategy Evaluation, the targets that have been set can be achieved with the ease of innovation that exists. The result is that strategic management in Surabaya's population governance has been running quite well but has not been optimized.